ANALYSIS OF DIFFERENT C:N RATIOS IN THE BIOFLOC SYSTEM ON THE GROWTH OF Pangasius hypophthalmus (Sauvage, 1878) - Sasry, Akbar Maulana; Supono, Supono; Wardiyanto, Wardiyanto (University of Lampung, 2020)
The development of catfish culture affects increasing waste in the waters. Aquaculture waste containing high nutrients has the potential to damage the cultivation environment. The Biofloc system in catfish farming can break down NH3 waste into flocks that can be consumed directly by fish. This study aims to analyze the growth and survival rate of catfish in biofloc systems with different C:N ratios. The research design used was a completely randomized design (CRD) with four treatments and three replications. Siamese catfish seeds were maintained in an aquarium container size 40 x 30 x 30 cm for 40 days with treatment media A (maintenance without biofloc), treatment B C:N ratio 15, treatment C C:N ratio 20, and treatment D C:N ratio 25. The results showed that the biofloc system with different C:N ratios had significant effect on the weight growth, daily growth rate, and feed convertion ratio of catfish. The best treatment for growth and viability of catfish is C:N ratio 25.